The review of the book called Rozmyślanie przemyskie. Świadectwo średniowiecznej kultury religijnej. Ed. Jerzy Bartmiński, Artur Timofiejew. Przemyśl 2016. s. 221: - - Wojtowicz, Małgorzata (Prace Polonistyczne, 2019)
The article is a scientific review of the book entitled Rozmyślanie przemyskie (The Przemyśl Meditation) edited by Jerzy Bartmiński, Artur Timofiejew, published in Przemyśl in 2016. The text discusses the structure of work and substantive content of individual 15 articles of researchers from various scientific centers in Poland, Russian and Ukraine. It can be noticed that the book has some innovative discoveries in the study of Polish literary heritage and plays an essential role in building scientific reflections not only on the subject of old Poland, but also Slavdom.